1930
DOI: 10.3181/00379727-27-4723
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of X-Ray Upon Bacteriophage and Upon the Bacterial Organism

Abstract: 285menbs were made of energy reflected by the epithelium inside the cheek, it may still be assumed that about one-third of the energy entering the cheek passed through.These studies indicate that living tissue is generally impermeable to all but a narrow b a d of ordinary radiant energy lying between wave lengths of 0.6 to 1.6 micron. Maximum penetration seems to occur at a wave length of 1.15 micron. What physiological or therapeutic effects such radiant energy has is still largely undetermined. A lamp specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1932
1932
1943
1943

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It would appear that x-rays either interfere with the growth and normal development of bacteria and yeasts, or produce a decided lethal effect according to many of the recent reports among which are those by Lacassagne (1928), Holweck (1929), Clark and Boruff (1929), Pauli and Sulger (1929), Holweck and Lacassagne (1930), Ellinger and Gruhn (1930), Wyckoff (1930a and1930b) and others. However, Beckwith, et al (1930) reported that the bacteria were not killed in their experiments. Curie (1929) and Glocker (1931) have discussed the bactericidal action of x-rays from the quantum standpoint.…”
mentioning
confidence: 99%
“…It would appear that x-rays either interfere with the growth and normal development of bacteria and yeasts, or produce a decided lethal effect according to many of the recent reports among which are those by Lacassagne (1928), Holweck (1929), Clark and Boruff (1929), Pauli and Sulger (1929), Holweck and Lacassagne (1930), Ellinger and Gruhn (1930), Wyckoff (1930a and1930b) and others. However, Beckwith, et al (1930) reported that the bacteria were not killed in their experiments. Curie (1929) and Glocker (1931) have discussed the bactericidal action of x-rays from the quantum standpoint.…”
mentioning
confidence: 99%
“…
Although much work has been done on the effects of X-rays on bacteria and other biologic materials, relatively little has been done on bacteriophages. Among the results reported is that of Beckwith, Olson and Rose (1930) who worked with six strains of Escherichia coli and seven Escherichia coli bacteriophages. They found that exposures to rays from a Roentgen tube for 30 minutes reduced, but did not destroy the lytic activity of 3 of the possible 42 combinations.
…”
mentioning
confidence: 99%